2022
DOI: 10.2166/wcc.2022.418
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic response of arid and semi-arid river basins in Iraq under a changing climate

Abstract: An assessment of the total hydrologic response of arid and semi-arid river basins to various scenarios of climate change by considering evapotranspiration, streamflow, and snowmelt is essential for sustainable management of water resources. The Diyala River Basin in Iraq has been chosen as a typical case study of dozens of river basins in arid and semi-arid regions. Here, the LASRS-WG, the Soil and Water Assessment Tool (SWAT), and the SWAT Calibration and Uncertainty Program (CUP) were used to evaluate the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The previous studies are supports this study's results according to (Kabobah et al, 2016), streamflow will change and decrease in the future due to climate change and its dependence on rainfall. Another study similarity suggests that future decreases in streamflow will be linked to projected decreases in precipitation (Saeed et al, 2022), as confirmed by this study's results. The change and decrease in streamflow shown by this study in the RCP 4.5 and RCP 8.5 global emissions scenarios are consistent with previous research (Amisigo et al, 2015).…”
Section: Impacts Of Climate Change On Future Annual and Seasonal Stre...supporting
confidence: 88%
“…The previous studies are supports this study's results according to (Kabobah et al, 2016), streamflow will change and decrease in the future due to climate change and its dependence on rainfall. Another study similarity suggests that future decreases in streamflow will be linked to projected decreases in precipitation (Saeed et al, 2022), as confirmed by this study's results. The change and decrease in streamflow shown by this study in the RCP 4.5 and RCP 8.5 global emissions scenarios are consistent with previous research (Amisigo et al, 2015).…”
Section: Impacts Of Climate Change On Future Annual and Seasonal Stre...supporting
confidence: 88%
“…In arid and semi-arid areas, water derived from the melting of snow and ice is the main source of riverine recharge (Li et al, 2013;Miller et al, 2021;Saeed et al, 2022). In the context of global warming, snow and glaciers melt rapidly, which increases streamflow, resulting in many snowmelt-based flood events (Liu et al, 2015;Uwamahoro et al, 2021).…”
Section: Hydrological Response Of Runoff To Snow Cover Changementioning
confidence: 99%
“…The Tmin, Tmax, wind speed, relative humidity, and solar radiation for Stations 1 and 2 were downloaded from Climate Forecasting System Reanalysis (CFSR). The CFSR weather data were recommended in SWAT applications in ungagged watersheds or missing data [40,32].…”
Section: Datamentioning
confidence: 99%
“…The projected streamflow modeled by Hilo et al [31] using the SWAT model and six Global Circulation Models (GCMs) indicated that the projected streamflow of Lesser Zab River tends to decline from 176.5 m 3 /s recorded in the period from 1980-2013 to 167 m 3 /s in the middle of the current century. Saeed et al [32] applied the Long Ashton Research Station-Weather Generator model (LARS-WG) and SWAT models in Diyala River basin using weather data for 2080 under five GCMs. The results indicated that streamflow of Diyala River tends to decrease by 38.8, 47.9, and 52.8% under Representative Concentration Pathways (RCPs) 2.6, 4.5, and 8.5, respectively, compared with observed streamflow recorded from 1990 to 2019.…”
Section: Introductionmentioning
confidence: 99%